Institutional Development Training for Freshwater Fish Farming Business Groups in Pombulaa Jaya Village, Konda District, South Konawe Regency - Supiyah, Ratna; Arsyad, Muhammad; Suaib, Eka; Hos, Jamaluddin; Bahtiar; Peribadi; Roslan, Suharty; Yusuf, Bakri; Sarpin; Ridwan, Harnina (CV. Literasi Indonesia, 2025)
Freshwater fish farming businesses face various obstacles, such as low knowledge and skills of fish farmers and limited access to the latest technology and information, which has an impact on productivity and crop quality. To overcome this problem, group institutional development training activities with a sociological approach are carried out to increase the capacity of fish farmers, strengthen coordination, and encourage the adoption of more efficient and sustainable farming practices. The method applied is participatory, by prioritizing collaboration between fish farmers and extension workers through discussions, technical training, and continuous assistance. The results of the activity showed that this training was effective in improving the technical skills of farmers, strengthening group coordination, and building collective awareness to adopt the latest innovations and technologies. Practically, this activity contributes to increasing the productivity and welfare of farmers, while theoretically, enriching the study of development sociology through the analysis of social interaction in the institution of farmer groups. Thus, strengthening institutional capacity and applying innovative technology is key to increasing the social and economic resilience of fish farmers sustainably.